STRATEGI KEUANGAN PERUSAHAAN YANG BERDAMPAK TERHADAP MASYARAKAT SEKITAR PADA PT SEMEN BATURAJA (PERSERO) TBK OGAN KOMERING ULU ( SUMATERA SELATAN ) - Puspita Sari, Iin; Safaruddin, Safaruddin; Prasetyo, Hendro (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Financial statements are reports that show the company's financial condition at this time or in a certain period. The company's financial statements need to be analyzed in order to obtain developments in the company's financial condition, including through analysis of financial ratios and comparative analysis of financial statements. The purpose of this final project is to find out the analysis of financial statements at PT Semen Baturaja (Persero) Tbk. The location of the observation was carried out at PT. Semen Baturaja ( Persero ) Tbk Financial Section, Ogan Komering Ulu Regency. Jl. Raya Tiga Gajah Kel. Sukajadi . East Baturaja District, Kab. Ogan Komering Ulu. The method used in this Final Project Report is a descriptive analysis method and data collection techniques in the form of observation, interviews and literature study. Based on financial report data at PT SEMEN BATURAJA Tbk, it shows that the company's financial condition is quite good because the company has increased profits every year, while the company's financial ratios have decreased in cash ratios and return on equity (ROE) but can increase these financial ratios